PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN, KOMPETENSI DAN KOMITMEN TERHADAP KINERJA PEGAWAI DINAS PENDIDIKAN DAN KEBUDAYAAN KOTA PALU - Rahma, Titi (Katalogis, 2017)
This research aims to find out and analyze the budgetery participation, competence, and commitment to the performance of education and cultural office staff of Palu City. Method used was multiple linear regression analysis assisted by statistics program SPSS 17.00. The resultsreveal that the budgetery participation, competence, and commitment significantly influence to the performance of staff, and commitment significantly influence to the performance of education and cultural office staff of Palu City.